Antarctic Animals in the Collection of Zoological Museum of the Ivan Franko National University of Lviv - Shydlovskyy, I.V. (Український антарктичний журнал, 2009)
The article presents a brief history of the formation and analysis of collections of Antarctic species of animals, which are stored in the Zoological Museum of Lviv National Ivan Franko University, and presented more than 300 specimens. У статті подано коротку історію формування та результати аналізу колекцій антарктичних видів тварин, які представлені більше ніж 300 зразками і зберігаються у Зоологічному музеї Львівського національного університету імені Івана Франка. В статье описана краткая история формирования и результаты анализа коллекций антарктических видов животных, которые представлены более чем 300 экспонатами и хранятся в Зоологическом музее Львовского национального университета имени Ивана Франко.